Addressing the Needs of Neglected Children and Victims of Exploitation: A Comprehensive Study on Policy, Ethical Considerations, and Survivor Em-powerment - Tan, Zhang Shen; Lee, Liu Tsai; Stewart , Baldry Pitre; Rauch, Levy (Law and Economics, 2023)
Exploitation of children, encompassing various forms of abuse, neglect, and violence, is a grave issue that demands urgent attention. This comprehensive research delves into the multifaceted dimensions of child exploitation, focusing on the experiences of neglected children and victims of exploitation, ethical considerations, and policy implications. The research employs a mixed-method approach, combining quantitative data analysis and qualitative interviews with survivors, advocates, and experts in the field. Findings reveal alarming prevalence rates, patterns of exploitation, and the profound impact on victims. The research underscores the need for policy reforms, better resource allocation, survivor empowerment, collaboration among stakeholders, and a survivor-centered approach. The ethical considerations involved in dealing with these sensitive cases emphasize the importance of informed consent, cultural sensitivity, and safeguarding the well-being and dignity of affected individuals. The implications of this research extend to global discussions on child protection and human rights, advocating for universal measures to safeguard children. In conclusion, this research serves as a clarion call for transformative changes in policies and interventions, aiming to create a more protective and supportive environment for neglected children and victims of exploitation.